Climate change, oil and gas development, and Inupiat whaling in northwest Alaska - Kishigami, Nobuhiro (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2010)
AbstractRelationships between human beings and whales vary temporally and spatially. The Inupiat in northwest Alaska have historically formed a social relationship with bowhead whales, which they hunt for their subsistence. Whaling still occupies a core position in the lives of the majority of the coastal Inupiat and is related to their other activities although their culture has diversified and changed. Using actor-network theory from a political economy perspective, this paper describes several interrelated internal and external factors (actors) that threaten the continuation of whaling. The author concludes that whaling is directly linked to the cultural security of the Inupiat.